Skin Application of Menthol Enhances Maximal Isometric Lifting Performance. Issue 3 (7th March 2023) - Over, Daniel M.; Arjomandkhah, Nicola; Beaumont, Jordan D.; Goodall, Stuart; Barwood, Martin J.
Abstract: Over, DM, Arjomandkhah, N, Beaumont, JD, Goodall, S, and Barwood, MJ. Skin application of menthol enhances maximal isometric lifting performance. J Strength Cond Res 37(3): 564–573, 2023—Topical application of menthol to the skin improves perception (i.e., makes subjects feel cooler) and changes submaximal neuromuscular recruitment facilitating force generation. We explored the effect of menthol (0.2% concentration; sprayed on the legs), on perception and maximal, dynamic (DLT) and isometric (IMLT) (weight) lifting tasks. Nine resistance-trained male subjects (mean ± SD : 24 ± 5 years; 75.7 ± 8.8 kg; 174 ± 10 cm; 5 repetition maximum deadlift [5RM] 132.3 ± 28.5 kg) were tested using a repeated measures design; we hypothesized that performance would improve. Before completing the DLT (i.e., deadlift performance 75% 1RM) and a midthigh pull dynamometer IMLT, subjects were sprayed with (∼125 ml) of menthol or control spray. Performance, electromyography (root mean squared [rmsEMG], rectus femoris [RF], biceps femoris [BF], and medial gastrocnemius [MG]), perceptions (leg thermal sensation [TSlegs ] and comfort [TClegs ] and perceived exertion [RPE] and readiness to train), heart rate, and skin temperature were measured. Data were compared using analysis of variance (effect size η p 2 ) and t test to a 0.05 alpha level supported by Bayesian analysis. Dynamic lifting task performance was unchanged, although BF rmsEMG was higher (i.e., greater muscle activation in final [10th] repetition). Isometric lifting task force production was higher in the menthol spray (148 ± 30 kgf) condition (control spray 140 ± 30 kgf; p = 0.035, η p 2 = 0.444) with corresponding higher rmsEMG (BF 3.8 ± 1.46 vs. control spray 2.9 ± 0.34 V; p = 0.049, η p 2 = 0.403). TSlegs was lower after menthol spray before IMLT; subjects felt slightly cool . Menthol spray enhances isometric weightlifting performance with corresponding changes in neuromuscular activity, partially supporting our hypothesis.